A High-Density Genetic Linkage Map and QTL Mapping for Sex and Growth-Related Traits of Large-Scale Loach (Paramisgurnus dabryanus) - Wei, Jin; Chen, Yuanyuan; Wang, Weimin (Frontiers in Genetics, 2019)
Large-scale loach (Paramisgurnus dabryanus) is a commercially important species in East Asia, however, the cultured population that exhibited degradation of germplasm resource cannot meet the market needs, and the genome resources for P. dabryanus are still lacking. In this study, the first high-density genetic map of P. dabryanus was constructed using 15,830 SNP markers based on high-throughput sequencing with an improved SLAF-seq strategy. The quantitative trait locus (QTL) mapping for sex, growth and morphology traits was performed for the first time. The genetic map spanned 4,657.64cM in length with an average inter-marker distance of 0.30 cM. QTL mapping and association analysis identified eight QTLs of growth traits, nine QTLs of morphology traits, and five QTLs of sex-related traits, respectively. Interestingly, the most significant QTLs for almost all the traits were concentrated on the same linkage group LG11. Seven candidate markers and 12 potentially key genes, which were associated with sex determination and growth, were identified within the overlapped QTL regions on LG11. Further, the first genome survey analysis of P. dabryanus was performed which represents the first step towards fully decoding the P. dabryanus genome. The genome scaffolds were anchored to the high-density linkage map, spanning 960.27 Mb of P. dabryanus reference genome. The collinearity analysis revealed a high level of collinearity between the genetic map and the reference genome of P. dabryanus. Moreover, a certain degree of homology was observed between large-scale loach and zebrafish using comparative genomic analysis. The constructed high-density genetic map was an important basis for QTL fine mapping, genome assembly, and genome comparison. The present study will provide a valuable resource for future marker-assisted breeding, and further genetic and genomic researches in P. dabryanus.